2018
DOI: 10.1177/1010539517753930
|View full text |Cite
|
Sign up to set email alerts
|

Incense Smoke and Increasing Carotid Intima Media Thickness: A Cross-Sectional Study of the Thai-Vietnamese Community

Abstract: Incense burning, a source of household indoor air pollution, is possible to effect on cardiovascular system. Our study sought to examine the association of long-term exposure to household incense smoke with increased carotid intima-media thickness (CIMT). A cross-sectional study was conducted 132 adults aged ≥35 years. Participants were stratified into 3 groups by their long-term household incense use; nonexposed group, non-daily exposed group, and daily exposed group. A combined mean CIMT (mean difference = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 30 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Epidemiologic studies have shown that long-term exposure to incense burning in the home environment is associated with an increased risk of cardiovascular mortality. One cross-sectional study showed that compared with non-users, daily users of incense had a higher prevalence of increased carotid intima-media thickness [14]. In our own study using data from the Singapore Chinese Health Study, we have also reported that daily exposure to incense burning at home for over 20 years was associated with a higher risk of cardiovascular mortality compared to non-users.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Epidemiologic studies have shown that long-term exposure to incense burning in the home environment is associated with an increased risk of cardiovascular mortality. One cross-sectional study showed that compared with non-users, daily users of incense had a higher prevalence of increased carotid intima-media thickness [14]. In our own study using data from the Singapore Chinese Health Study, we have also reported that daily exposure to incense burning at home for over 20 years was associated with a higher risk of cardiovascular mortality compared to non-users.…”
Section: Discussionmentioning
confidence: 69%
“…A study in the United Arab Emirates reported that 86.0% of the participants were exposed to incense smoke at least once a week and 44.0% of them were exposed daily [33]. Studies in China (76.1%), India (78.0%) and Thailand (67.4%) also reported high proportions of current incense users in their respective study populations [6, 14, 34]. In our study in Singapore, the prevalence of current incense use was 76.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one can extrapolate that pollution exposure is inevitable in this study population. Another limitation was we could measure only mean CIMT in this study although some scholars performed measuring mean and maximal CIMT [ 29 , 34 ]. Moreover, CIMT measurement was done at a single time point, which requires follow-ups measurements to explore CIMT levels throughout pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Factors adjusted for Model a and Model b were in the fully adjusted model. Potential covariates were selected on the basis of evidences in recent publications [29][30][31].…”
Section: Discussionmentioning
confidence: 99%